Mengatasi Rendahnya Disiplin Belajar Siswa Dalam Pembelajaran Daring Pada Masa Pandemi Covid-19 Melalui Konseling Behavioristik Teknik Self Management - Nur Aeni Septianingrum; Arista Kiswantoro; Susilo Rahardjo (Jurnal Muria Research Guidance and Counseling (MRGC), 2022)
The aims of this study are: 1. To describe the causes of lack of self-discipline in online learning during the COVID-19 pandemic by PGRI 2 Kayen High School students, 2. To overcome the low self-discipline of students in online learning during the COVID-19 pandemic with technical behavioristic counseling. self-management.The type of research used is a case study of guidance and counseling. The subjects studied in class XI IPA 5 were two students who had low learning discipline behavior in online learning. Data collection methods used are methods: observation, interviews, and documentation. Data analysis used bacon system induction analysis.The results of the research there are two factors: 1) Internal factors, students do not have interest, feel lazy, lack motivation, 2) external factors, from outside students lack parental attention and encouragement. After conducting behavioristic counseling with self-management techniques, the counselee can show a change in more disciplined learning in online learning.